Amplification and Analysis of Cytocrome Oxidase I of Polypedates leucomystax from Bogor Agricultural University Area - Perkasa Arian; I Made Artika; Syamsul Falah (IPB University, 2016)
DNA barcoding has become a useful tool for identifying and confirming of species within a known taxonomic framework. A large-scale effort is underway to barcode all amphibian species using the universally sequenced DNA region, a partial fragment of mitochondrial cytochrome oxidase subunit I (COI). This study was aimed to use DNA barcoding technique to identify and confirm species of Polypedates leucomystax and to analyze their phylogenetic relationship. Samples of Polypedates leucomystax were collected from Campus Area of Bogor Agricultural University. The cytochrome oxidase I gene of 600-700 nucleotides were amplified and observed in agarose gel electrophoresis. Forward sequence (604 base pairs) of COI gene was used for phylogenetic analyses. BLAST analysis against BOLD System database showed 95.75% identity with sequences of Polypedates leucomystax. The pairwise genetic distances of Polypedates leucomystax with Rhacophorus schlegelii, Limnonectes fujianensis, Fejervarya cancrivora, and Bufo melanostictus were 0.274, 0.352, 0.339, 0.339, 0.393, respectively. These results illustrated that the genetic identification is congruence with the morphological identification. Phylogenetic tree analysis showed that the samples were in one clade with other tree frogs. The DNA barcoding technique based on the sequence of COI gene can therefore be used to identify and confirm species of Polypedates leucomystax.